Multi-layer spraying paper-based material for food packaging

By using a multi-layer spraying technology of maleic acid-polyvinyl alcohol-starch cross-linking layer, oxidized nanocellulose layer and nanocellulose layer in food packaging paper-based materials, the shortcomings of existing paper-based materials in water vapor barrier, mechanical properties and durability are solved, and higher barrier properties and mechanical properties are achieved.

CN119553546APending Publication Date: 2025-03-04TIANJIN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411702323.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing barrier paper-based materials for food packaging have shortcomings in water vapor barrier, mechanical properties and durability, which leads to easy damage, leakage or contamination during food transportation.

Method used

The primary paper layer, maleic acid-polyvinyl alcohol-starch cross-linking layer, oxidized nanocellulose layer, and nanocellulose layer are sprayed layer by layer. Through the cross-linking effect of maleic acid on starch and polyvinyl alcohol, the barrier rate of oxygen and water vapor and the durability and mechanical properties of paper-based materials are synergistically improved.

Benefits of technology

The barrier properties, breakage index, tensile index and fold resistance of paper-based materials are significantly improved, and they show excellent performance as food packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005153650210000071
    Figure BDA0005153650210000071
Patent Text Reader

Abstract

Belongs to the technical field of light industry, and discloses a multilayer spraying paper-based material for food packaging, which comprises a raw paper layer, a maleic acid-polyvinyl alcohol-starch crosslinking layer, an oxidized nano cellulose layer and a nano cellulose layer from bottom to top in sequence, the total spraying quantity of the maleic acid-polyvinyl alcohol-starch crosslinking layer, the oxidized nanocellulose layer and the nanocellulose layer is 40-60g / m < 2 >. The paper-based material produced by the invention has good oxygen barrier, moisture barrier and mechanical properties, and the used spraying material is green, environment-friendly and biodegradable, has small harm to the environment and human body, and can be used for food packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of light industry science and technology, and specifically relates to a multi-layer spray-coated paper-based material for food packaging. Background Art

[0002] Barrier paper-based materials have great potential in replacing plastic packaging materials due to their biodegradable and environmentally friendly properties. Using barrier paper-based materials in food packaging can significantly reduce the use of packaging plastics, reduce environmental pollution and waste of resources.

[0003] Although existing barrier paper-based materials used for food packaging have many advantages, such as environmental protection, recyclability, light weight and portability, they also have some disadvantages in practical applications, such as poor water vapor barrier performance, insufficient mechanical properties and durability issues under extreme conditions. During food transportation, paper-based materials are easily damaged or cracked, causing food leakage or contamination. Especially for liquid or wet foods, the weak wet strength of paper-based materials may cause the packaging to lose its sealing, further affecting the storage and transportation safety of food. Therefore, barrier, mechanical properties and durability are extremely important for the widespread application of barrier paper-based materials.

[0004] Chinese patent CN117364542A discloses a water-proof, oil-resistant and anti-sticking food plastic substitute packaging paper, as well as a preparation method and application thereof. The food plastic substitute packaging paper adopts a multi-layer composite structure design, including an inner layer, an intermediate layer and a surface layer composited in sequence; the inner layer is a base paper layer, the intermediate layer is a starch layer, and the surface layer is a waterproof and oil-proof barrier coating; the waterproof and oil-proof barrier coating is prepared by coating a mixture of an aqueous acrylic resin emulsion and a biodegradable filler; although the packaging paper prepared by this patent can be used for food packaging, the starch layer has poor mechanical properties and poor durability during use.

[0005] Chinese patent CN110747699A discloses a food packaging paper and a preparation method thereof, comprising: a base paper layer; a barrier layer arranged on the base paper layer; the barrier layer comprises an impermeable layer and a protective layer; the impermeable layer is in contact with the base paper layer; the impermeable layer is formed of a water-soluble polymer; and the protective layer is formed of a resin composition.

[0006] The above-mentioned thermoplastic resin surface lamination and latex impregnation can improve the barrier effect of paper-based materials, but these two methods add more organic matter, which will make the recycling of paper products difficult and not environmentally friendly enough, and the barrier and mechanical properties of paper-based materials need to be improved.

[0007] Therefore, there is a need for a paper-based material for food packaging that is excellent in environmental protection, mechanical properties, and barrier properties. Summary of the invention

[0008] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a multi-layer spray-coated paper-based material for food packaging. The material is sprayed layer by layer in the order of a base paper layer, a maleic acid-polyvinyl alcohol-starch cross-linked layer, an oxidized nanocellulose layer, and a nanocellulose layer. Through the cross-linking effect of maleic acid on starch and polyvinyl alcohol, the synergistic effect of the maleic acid-polyvinyl alcohol-starch cross-linked layer and the oxidized nanocellulose layer improves the barrier rate of oxygen and water vapor and the durability and mechanical properties of the paper-based material.

[0009] The purpose of the present invention is achieved by adopting the following technical solutions:

[0010] The invention provides a multi-layer spray-coated paper-based material for food packaging, comprising: a base paper layer, a maleic acid-polyvinyl alcohol-starch cross-linked layer, an oxidized nanocellulose layer, and a nanocellulose layer, which are arranged in sequence from bottom to top; the total spraying amount of the maleic acid-polyvinyl alcohol-starch cross-linked layer, the oxidized nanocellulose layer, and the nanocellulose layer is 40 to 60 g / m 2 .

[0011] Furthermore, the preparation method of the multi-layer spray-coated paper-based material is:

[0012] (1) heating a starch and glycerol blend solution containing 2 to 4% solids at 90 to 95° C. in a water bath for gelatinization for 0.4 to 0.6 h, adding a polyvinyl alcohol solution containing 3 to 6% solids and a maleic acid solution containing 1 to 3% solids in sequence after gelatinization, stirring magnetically at room temperature for 1 h, and then spraying the solution evenly on a base paper layer, drying the solution at 45 to 55° C. for 8 to 15 min, and drying to obtain a base paper layer, a maleic acid-polyvinyl alcohol-starch cross-linking layer composite paper base material;

[0013] (2) mixing 1-2% solid content oxidized nanocellulose and glycerol and spraying the mixture evenly on the maleic acid-polyvinyl alcohol-starch crosslinked layer of the paper-based material in step (1), drying at 75-90° C. for 35-45 min to obtain a paper-based material composed of a base paper layer, a maleic acid-polyvinyl alcohol-starch crosslinked layer, and an oxidized nanocellulose layer;

[0014] (3) mixing nanocellulose with a solid content of 1 to 2% and glycerol and spraying the mixture evenly on the oxidized nanocellulose layer of the paper-based material in step (2), drying the mixture at 75 to 90° C. for 35 to 45 minutes, and drying the mixture to obtain a paper-based material having a base paper layer, a maleic acid-polyvinyl alcohol-starch crosslinking layer, an oxidized nanocellulose layer, and a nanocellulose layer;

[0015] (4) Drying the paper base material obtained in step (3), calendering the paper sample, and obtaining a multi-layer spray-coated paper base material.

[0016] Furthermore, the starch is sweet potato starch.

[0017] Furthermore, the starch and glycerol blend solution is prepared by adding absolute dry starch to water and then adding glycerol, and the mass ratio of the starch to glycerol is 1 to 5:1.

[0018] Furthermore, the spraying amount of the maleic acid solution in the maleic acid-polyvinyl alcohol-starch cross-linking layer is 3 to 5 g / m 2 The spraying quantity of polyvinyl alcohol solution is 2.5~10g / m 2 The starch solution spraying quantity is 10~17.5g / m 2 .

[0019] Furthermore, the mass ratio of the oxidized nanocellulose / nanocellulose and glycerol is 1:4 to 1:5.

[0020] Furthermore, the spraying amount of the oxidized nanocellulose layer is 18-22 g / m 2 The spraying amount of nanocellulose layer is 3-8g / m 2 .

[0021] Furthermore, the base paper layer uses bagasse pulp as a raw material for sheet making, and the paper basis weight is 220-240 g / m 2 .

[0022] Polyvinyl alcohol (PVA) is a synthetic water-soluble polymer with high oxygen barrier capacity, good heat resistance, good adhesion and biocompatibility, good water solubility and biodegradability, excellent film-forming ability and transparency. Due to its high hydroxyl content, it is an ideal coating material for applications such as paper-based packaging and barrier materials. Starch is a biopolymer that is widely used in packaging to reduce environmental pollution due to its affordability, abundance, non-toxicity, renewability and biodegradability. However, pure starch has various disadvantages, such as insufficient strength, low thermal stability, brittleness, easy aging and difficulty in film formation. Therefore, blending starch and PVA can improve the mechanical properties, barrier properties and film-forming properties of starch, but starch and PVA are incompatible with each other, and plasticizers need to be introduced to enhance the properties of starch / PVA films.

[0023] The present application uses a maleic acid solution mixed with a starch solution and polyvinyl alcohol to prepare a maleic acid-polyvinyl alcohol-starch cross-linked layer. Starch and PVA contain a large number of hydroxyl groups. Maleic acid can not only enhance the cross-linking effect of starch and PVA, but also maleic acid is a cheap and non-toxic chemical. Appropriate addition of food-grade maleic acid can enhance the special fruit flavor in food and beverages and improve the taste.

[0024] Nanocellulose is a nano-sized cellulose material that has the characteristics of high strength, light weight, renewability, and biodegradability. Nanocellulose as a paper coating can improve the strength, toughness, and durability of paper.

[0025] Oxidized nanocellulose is a type of nanocellulose that has been TEMPO-oxidized and has a large number of carboxyl groups on its surface, which enhances its hydrophilicity and reactivity. Oxidized nanocellulose has high strength and toughness, and can significantly improve the tear and abrasion resistance of paper. Due to the porous structure of oxidized nanocellulose, the coated paper can better block moisture and gas penetration, improving moisture resistance and freshness preservation.

[0026] The barrier paper-based material of the present invention is prepared by spraying layer by layer in strict order of a base paper layer, a maleic acid-polyvinyl alcohol-starch cross-linking layer, an oxidized nanocellulose layer, and a nanocellulose layer. The maleic acid-polyvinyl alcohol-starch cross-linking layer is a bottom coating layer of paper and fills the pores between paper fibers. Maleic acid is used to form a network structure of starch and polyvinyl alcohol through cross-linking, so that the coating is more tightly combined and a smooth interface is provided for the next layer. Oxidized nanocellulose and nanocellulose are sprayed layer by layer on the maleic acid-polyvinyl alcohol-starch cross-linking layer. Since the oxidized nanocellulose has a large number of carboxyl groups on its surface, it can be hydrogen-bonded with the maleic acid-polyvinyl alcohol-starch cross-linking layer and the nanocellulose layer, thereby enhancing the synergistic effect between the three layers, improving the barrier property to oxygen and water vapor, and also providing good mechanical properties for the paper-based material.

[0027] The advantages and beneficial effects of the present invention are:

[0028] (1) The paper-based material of the present invention has excellent oxygen and water vapor barrier properties and excellent bursting index, tensile index, and folding resistance, and can be used as a good food packaging material.

[0029] (2) The amount of maleic acid and polyvinyl alcohol added in the present invention is relatively small, and starch, nanocellulose, and oxidized nanocellulose are all biomass materials and are degradable. The preparation process is simple and easy, the practicability is strong, and the food packaging material is more environmentally friendly and easy to promote. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0031] Example 1

[0032] A method for preparing a multi-layer spray-coated paper-based material for food packaging, comprising:

[0033] (1) Coating of maleic acid-polyvinyl alcohol-starch cross-linked layer:

[0034] Add 3 g of absolutely dry sweet potato starch to 100 g with water to obtain a sweet potato starch solution with a solid content of 3%, then add 1.5 g of glycerol, heat in a water bath, gelatinize at 95° C. for 0.5 h, and obtain a gelatinized sweet potato starch and glycerol blend solution;

[0035] A maleic acid solution with a solid content of 2% and a polyvinyl alcohol solution with a solid content of 5%, sweet potato starch and glycerol mixed solution were mixed, wherein the spraying quantity of the maleic acid solution was 4g / m 2 The spraying quantity of polyvinyl alcohol solution is 2.5g / m 2 The starch spraying quantity is 17.5g / m 2 The mixture was magnetically stirred at room temperature for 1 h.

[0036] The basis weight is 240g / m 2 Spray the maleic acid-polyvinyl alcohol-starch mixture on one side of the paper and dry it at a drying temperature of 50°C for 10 minutes. Be careful not to cause wrinkles and keep the paper surface as flat as possible to obtain a paper-based material composed of a base paper layer and a maleic acid-polyvinyl alcohol-starch cross-linking layer.

[0037] (2) Coating of oxidized nanocellulose layer:

[0038] 1 g of oxidized nanocellulose was added with water to obtain 100 g of oxidized nanocellulose solution with a solid content of 1%, and 5 g of glycerol was added and mixed to obtain a mixed solution of oxidized nanocellulose and glycerol;

[0039] The oxidized nanocellulose and glycerol blend solution was heated at 20 g / m 2 The quantitative coating is sprayed on the basis of the maleic acid-polyvinyl alcohol-starch cross-linked layer and dried at a temperature of 80°C and a drying time of 40 minutes. During the process, the paper surface is kept as flat as possible to obtain a paper-based material composited with a base paper layer, a maleic acid-polyvinyl alcohol-starch cross-linked layer and an oxidized nanocellulose layer.

[0040] (3) Coating of nanocellulose layer:

[0041] Add water to 100 g of nanocellulose, add 5 g of glycerol, mix well to obtain a nanocellulose solution with a solid content of 1%, then add 5 g of glycerol, mix well to obtain a nanocellulose and glycerol blend solution;

[0042] The nanocellulose and glycerol blend solution was heated to 5 g / m 2 The quantitative coating is sprayed on the basis of the oxidized nanocellulose coating and dried at a temperature of 80°C for 40 minutes. During the process, the paper surface is kept as flat as possible to prepare a multi-layer spray-coated paper-based material composed of a base paper layer, a maleic acid-polyvinyl alcohol-starch cross-linked layer, an oxidized nanocellulose layer, and a nanocellulose layer.

[0043] Example 2

[0044] A method for preparing a multi-layer spray-coated paper-based material for food packaging, comprising:

[0045] (1) Coating of maleic acid-polyvinyl alcohol-starch cross-linked layer:

[0046] The blended solution of sweet potato starch and glycerol is the same as that in Example 1;

[0047] A 2% maleic acid solution and a 5% polyvinyl alcohol solution, sweet potato starch and glycerol blend solution were mixed, wherein the spraying quantity of the maleic acid solution was 4 g / m 2 The spraying quantity of polyvinyl alcohol solution is 3.3g / m 2 The starch spraying quantity is 16.7g / m 2 The mixture was magnetically stirred at room temperature for 1 h for later use;

[0048] The basis weight is 240g / m 2 Spray the maleic acid-polyvinyl alcohol-starch mixture on one side of the paper and dry it at a drying temperature of 50°C for 10 minutes. Be careful not to cause wrinkles and keep the paper surface as flat as possible to obtain a paper-based material composed of a base paper layer and a maleic acid-polyvinyl alcohol-starch cross-linking layer.

[0049] (2) Coating of oxidized nanocellulose layer:

[0050] The oxidized nanocellulose and glycerol blend solution was the same as in Example 1. The oxidized nanocellulose and glycerol blend solution was mixed at 20 g / m 2 The quantitative coating is sprayed on the basis of the maleic acid-polyvinyl alcohol-starch cross-linked layer and dried at a temperature of 80°C and a drying time of 40 minutes. During the process, the paper surface is kept as flat as possible to obtain a paper-based material composited with a base paper layer, a maleic acid-polyvinyl alcohol-starch cross-linked layer and an oxidized nanocellulose layer.

[0051] (3) Coating of nanocellulose layer:

[0052] The nanocellulose and glycerol blend solution is the same as in Example 1. The nanocellulose and glycerol blend solution is 5 g / m 2 The quantitative amount of the oxidized nanocellulose coating was sprayed and dried at 80 ° C for 40 min. During the process, the paper surface was kept flat as much as possible to prepare a base paper layer, a maleic acid-polyvinyl alcohol-starch cross-linked layer, an oxidized nanocellulose layer, and a nanocellulose layer composite multilayer spray coating.

[0053] Paper-based material.

[0054] Example 3

[0055] A method for preparing a multi-layer spray-coated paper-based material for food packaging, comprising:

[0056] (1) Coating of maleic acid-polyvinyl alcohol-starch cross-linked layer:

[0057] The sweet potato starch and glycerol blend solution is the same as in Example 1, wherein 2% maleic acid solution, 5% polyvinyl alcohol solution, and sweet potato starch and glycerol blend solution are mixed, wherein the spraying quantity of the maleic acid solution is 4 g / m 2 The spraying quantity of polyvinyl alcohol solution is 5g / m 2 The starch spraying quantity is 15g / m 2 The mixture was magnetically stirred at room temperature for 1 h for later use;

[0058] The basis weight is 240g / m 2 Spray maleic acid-polyvinyl alcohol-starch mixture on one side of the paper and dry it at 50°C for 10 minutes. Be careful not to cause wrinkles and keep the paper surface as flat as possible.

[0059] (2) Coating of oxidized nanocellulose layer:

[0060] Add water to 100 g of nanocellulose TOCNF 1 g, then add 5 g of glycerol, and mix well to obtain a nanocellulose TOCNF solution with a solid content of 1%;

[0061] A 1% solid content of nanocellulose TOCNF solution was prepared at 20 g / m 2 The quantitative amount is sprayed on the basis of starch coating and dried. The drying temperature is 80℃ and the drying time is 40min. During the process, the paper surface is kept flat as much as possible.

[0062] (3) Coating of nanocellulose layer:

[0063] The nanocellulose and glycerol blend solution is the same as in Example 1. The nanocellulose and glycerol blend solution is 5 g / m 2 The quantitative coating is sprayed on the basis of the oxidized nanocellulose coating and dried at a temperature of 80°C for 40 minutes. During the process, the paper surface is kept as flat as possible to prepare a multi-layer sprayed paper-based material.

[0064] Example 4

[0065] A method for preparing a multi-layer spray-coated paper-based material for food packaging, comprising:

[0066] (1) Coating of maleic acid-polyvinyl alcohol-starch cross-linked layer:

[0067] Sweet potato starch solution and glycerol are mixed as in Example 1, 2% maleic acid solution and 5% polyvinyl alcohol solution, starch and glycerol mixed solution are mixed, wherein the spraying quantity of maleic acid solution is 4g / m 2 The spraying quantity of polyvinyl alcohol solution is 10g / m 2 The starch spraying quantity is 10g / m 2 The mixture was magnetically stirred at room temperature for 1 h for later use;

[0068] The basis weight is 240g / m 2 Spray maleic acid-polyvinyl alcohol-starch mixture on one side of the paper and dry it at 50℃ for 10 minutes. Be careful not to wrinkle it and keep the paper as thin as possible.

[0069] The surface is leveled to obtain a paper-based material composed of a base paper layer and a maleic acid-polyvinyl alcohol-starch cross-linking layer;

[0070] (2) Coating of oxidized nanocellulose layer:

[0071] The oxidized nanocellulose and glycerol blend solution was the same as in Example 1. The oxidized nanocellulose and glycerol blend solution was mixed at 20 g / m 2 The quantitative coating is sprayed on the basis of the maleic acid-polyvinyl alcohol-starch cross-linking layer and dried at a drying temperature of 80°C and a drying time of 40 minutes. During the process, the paper surface is kept as flat as possible.

[0072] (3) Coating of nanocellulose layer:

[0073] The nanocellulose and glycerol blend solution is the same as in Example 1. The nanocellulose solution and glycerol are blended at 5 g / m 2 The quantitative coating is sprayed on the basis of the oxidized nanocellulose coating and dried at a temperature of 80°C for 40 minutes. During the process, the paper surface is kept as flat as possible to prepare a multi-layer sprayed paper-based material.

[0074] Comparative Example 1

[0075] The only difference from Example 1 is that, in step (1) of the preparation method, the sweet potato starch and glycerol blend solution is the same as that of Example 1;

[0076] A polyvinyl alcohol solution with a solid content of 5%, sweet potato starch and glycerol blend solution were mixed, wherein the spraying quantity of the polyvinyl alcohol solution was 6.5 g / m 2 The starch spraying quantity is 17.5g / m 2 The mixture was magnetically stirred at room temperature for 1 h for later use;

[0077] The basis weight is 240g / m 2Spray the polyvinyl alcohol-starch mixture on one side of the paper and dry it at a drying temperature of 50°C for 10 minutes. Be careful not to cause wrinkles and keep the paper surface as flat as possible to obtain a paper-based material composed of a base paper layer and a polyvinyl alcohol-starch cross-linking layer.

[0078] Comparative Example 2

[0079] A multi-layer spray-coated paper-based material for food packaging comprises a base paper layer, an oxidized nanocellulose layer, a maleic acid-polyvinyl alcohol-starch cross-linking layer, and a nanocellulose layer arranged in sequence from bottom to top; a preparation method comprises:

[0080] (1) Coating of oxidized nanocellulose layer:

[0081] The oxidized nanocellulose and glycerol blend solution was the same as in Example 1. The oxidized nanocellulose and glycerol blend solution was mixed at 20 g / m 2 The quantitative spraying is 240g / m 2 The paper is dried on one side at a temperature of 50° C. for 10 min. During the process, the paper surface is kept as flat as possible to obtain a paper-based material composited with a base paper layer and an oxidized nanocellulose layer.

[0082] (2) Coating of maleic acid-polyvinyl alcohol-starch cross-linking layer:

[0083] The sweet potato starch and glycerol blend solution is the same as in Example 1, wherein a 2% solid content maleic acid solution, a 5% solid content polyvinyl alcohol solution, and a sweet potato starch and glycerol blend solution are mixed, wherein the spraying quantity of the maleic acid solution is 4 g / m 2 The spraying quantity of polyvinyl alcohol solution is 2.5g / m 2 The starch spraying quantity is 17.5g / m 2 The mixture was magnetically stirred at room temperature for 1 h.

[0084] The maleic acid-polyvinyl alcohol-starch mixed solution is sprayed on the oxidized nanocellulose layer of the paper-based material prepared in step (1), and then sprayed and dried at a drying temperature of 80° C. for 40 minutes. During the process, the paper surface is kept as flat as possible to obtain a paper-based material composed of a base paper layer, an oxidized nanocellulose layer, and a maleic acid-polyvinyl alcohol-starch cross-linked layer.

[0085] Oxygen transmission rate refers to the amount of oxygen permeating through a unit area of ​​a sample under a specified pressure difference and time, and the unit is cm 3 / cm 2·d·bar. The test principle is: clamp the sample between the upper and lower test chambers of the test instrument, first vacuum the lower chamber (low-pressure chamber), then evacuate the entire system, close the lower chamber after a certain period of time, fill the upper chamber (high-pressure chamber) with a certain pressure of high-purity oxygen (purity is 99.99%), and ensure that a constant pressure difference is formed on both sides of the sample. Under the action of the pressure gradient, oxygen penetrates from the high-pressure side to the low-pressure side. By monitoring the internal pressure of the low-pressure side, the oxygen permeability of the tested sample can be obtained.

[0086] The water vapor transmission rate tester measures the water vapor transmission rate of paper. The test conditions are: temperature T = 23°C, and relative humidity is controlled at 50%.

[0087] Table 1 Oxygen permeability and water permeability of barrier paper-based materials prepared in Examples and Comparative Examples

[0088]

[0089] It can be seen from the data in Table 1 that the oxygen permeability and water permeability of the paper-based material prepared by the polyvinyl alcohol-starch cross-linked layer in Comparative Example 1 are not as good as those in the embodiment, indicating that the addition of maleic acid improves the oxygen and moisture barrier effects of the maleic acid-polyvinyl alcohol-starch cross-linked layer and the oxidized nanocellulose layer. In Comparative Example 2, the maleic acid-polyvinyl alcohol-starch cross-linked layer and the oxidized nanocellulose layer are sequentially exchanged, and the water vapor and oxygen permeability values ​​are not as good as those in the embodiment, indicating that the cross-linking effect of maleic acid on starch and polyvinyl alcohol makes the bonding between the coatings tighter. At the same time, the addition of maleic acid can enhance the cross-linking effect between maleic acid-polyvinyl alcohol-starch, enhance the interaction between the three layers, and improve the barrier property to water vapor.

[0090] Before testing the mechanical properties of the paper samples, the paper samples were first placed in the international standard constant temperature (23±1)°C and constant humidity (50±2)% experimental conditions for 4 hours to balance the moisture content of the paper samples.

[0091] Tensile index test:

[0092] Cut several paper strips with a width of (15.0±0.1)mm and a length of not less than 150mm. The samples should not have creases, wrinkles, folds or other factors that affect the thickness. The cut paper samples are measured with a tensile strength meter. Generally, the testing time is 15 to 25 seconds for valid data.

[0093] Burst index test:

[0094] The size of each specimen shall not be less than 70mmc×70mm, and the specimen shall not have folds, wrinkles, visible cracks or other obvious damage.

[0095] Folding endurance test:

[0096] Place the paper sample between the clamps. Under a certain tension, the lower clamp is swung left and right to make the sample fold back and forth within a certain angle. As the number of folds increases, the strength of the sample gradually decreases until it breaks when it can no longer withstand the spring tension. The number of folds when it breaks is the folding endurance of the sample.

[0097] Mechanical property tests were conducted on Examples 1 to 4 and Comparative Examples 1 to 2, and the bursting index, tensile index, and folding endurance of the paper samples were tested respectively. The data are shown in Table 2.

[0098] Table 2 Mechanical properties test results of Examples 1 to 4 and Comparative Examples 1 to 2

[0099] Paper Pattern <![CDATA[Bursting strength index (kPa·m 2 / g)]]> Tensile index (N·m / g) Folding endurance (times) Example 1 2.02 19.7 395 Example 2 2.36 22.2 590 Example 3 2.66 24.4 807 Example 4 2.83 27.1 971 Comparative Example 1 1.48 11.9 202 Comparative Example 2 1.92 16 300

[0100] According to the data in Table 2, it can be seen that the paper-based materials prepared in Examples 1 to 4 have better mechanical properties than those in the comparative examples, indicating that maleic acid can enhance the cross-linking effect of starch and PVA, and can also enhance the bonding effect between the maleic acid-polyvinyl alcohol-starch cross-linking layer and the oxidized nanocellulose layer, thereby enhancing the interaction between the three layers, thereby improving the tensile index, bursting index and folding endurance of the paper-based material.

[0101] The above descriptions are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications.

Claims

1. A multi-layer spray-coated paper-based material for food packaging, characterized in that: The method comprises sequentially arranging a base paper layer, a maleic acid-polyvinyl alcohol-starch cross-linked layer, an oxidized nanocellulose layer, and a nanocellulose layer from bottom to top; the total spraying amount of the maleic acid-polyvinyl alcohol-starch cross-linked layer, the oxidized nanocellulose layer, and the nanocellulose layer is 40 to 60 g / m 2 .

2. The multi-layer spray-coated paper-based material according to claim 1, characterized in that: The preparation method of the multi-layer spray-coated paper-based material is as follows: (1) heating a starch and glycerol mixed solution with a solid content of 2-4% at 90-95° C. in a water bath for gelatinization for 0.4-0.6 h, adding polyvinyl alcohol with a solid content of 3-6% and a maleic acid solution with a solid content of 1-3% in sequence after gelatinization, stirring magnetically at room temperature for 1 h, and then spraying the solution evenly on base paper, and drying the solution at 45-55° C. for 8-15 min to obtain a paper-based material having a base paper layer and a maleic acid-polyvinyl alcohol-starch cross-linking layer; (2) mixing 1-2% solid content oxidized nanocellulose and glycerol and spraying the mixture evenly on the maleic acid-polyvinyl alcohol-starch crosslinked layer of the paper-based material in step (1), drying at 75-90° C. for 35-45 min to obtain a paper-based material composed of a base paper layer, a maleic acid-polyvinyl alcohol-starch crosslinked layer, and an oxidized nanocellulose layer; (3) mixing nanocellulose with a solid content of 1 to 2% and glycerol and spraying the mixture evenly on the oxidized nanocellulose layer of the paper-based material in step (2), drying the mixture at 75 to 90° C. for 35 to 45 minutes, and drying the mixture to obtain a paper-based material having a base paper layer, a maleic acid-polyvinyl alcohol-starch crosslinking layer, an oxidized nanocellulose layer, and a nanocellulose layer; (4) Drying the paper base material obtained in step (3), calendering the paper sample, and obtaining a multi-layer spray-coated paper base material.

3. The multi-layer spray-coated paper-based material according to claim 2, characterized in that: The starch is sweet potato starch, and the starch and glycerol blend solution is prepared by adding absolute dry starch into water and then adding glycerol. The mass ratio of the starch to the glycerol is 1 to 5:

1.

4. The multi-layer spray-coated paper-based material according to claim 2, characterized in that: The spraying quantity of maleic acid in the maleic acid-polyvinyl alcohol-starch cross-linking layer is 3-5 g / m 2 The spraying quantity of polyvinyl alcohol is 2.5~10g / m 2 The starch spraying quantity is 10~17.5g / m 2 .

5. The preparation method according to claim 2, characterized in that: The spraying amount of the oxidized nanocellulose layer is 18-22 g / m 2 The spraying quantity of nanocellulose coating is 3-8g / m 2 The drying time is 35-45 minutes and the drying temperature is 75-90°C.

6. The multi-layer spray-coated paper-based material according to claim 2, characterized in that: The base paper layer uses bagasse pulp as a raw material for sheet making, and the paper basis weight is 220-240g / m 2 .

Citation Information

Patent Citations

  • Food wrapping paper and preparation method thereof

    CN110747699A

  • Food plastic-substituted packaging paper capable of blocking water and oil and resisting anti-sticking as well as preparation method and application of food plastic-substituted packaging paper

    CN117364542A